Sharia Consumption Ethics Analysis on “Buying the Good Product Campaign” Of World-Wide Fund for Nature (WWF) Indonesia - Sunardi; Nur Jamaludin; Nurul Mulia Wati (Proceeding International Conference on Religion, Science and Education, 2023)
Islam encourages individuals to protect not only the earth but also the natural environment. The research titled "Sharia Consumer Ethics Analysis on Buying the Good Product Campaign of WWF Indonesia" identifies an issue with the applicability of sharia consumption ethics to the WWF-Indonesia-initiated "Buying the Good" program. The purpose of this qualitative study is to evaluate the applicability of sharia consumption ethics to WWF-Buying Indonesia’s The Good Product Campaign. This research utilizes two types of data: primary data obtained through interviews and secondary data obtained from books and internet sources. The informants, who are Superindo Intercon customers, were selected using a method of purposeful sampling. The data was then verified by Superindo Intercon’s store manager and Sharia economics experts. The results indicate that the sharia ethics of consumption and "purchasing the good program" are compatible. In addition, consumers understand the sharia ethics of consumption through various campaigns under the "Buy the Good" program, such as buying necessary products, buying local products, buying natural products, buying long-lasting products, buying eco-friendly products, and knowing where to bring the consumption residue. To engage in responsible and ethical consumerism, however, it is necessary to have access to environmentally friendly products. Therefore, consumers, manufacturers, and governments should collaborate to establish such ethical and responsible consumption.